Development of boronized duplex stainless steel mini gear through superplastic deformation / Hassanuddin Ismail - Hassanuddin, Ismail (2013)
In this work, formation of mini gear with superplastic deformation on boronized duplex stainless steel (DSS) was studied through the employment of these quantifying factors, i.e. strains and strain rates. As received DSS specimen was thermo-mechanically treated by heating up to 1537K, holding for one hour, followed by water quenching and then cold rolled to a plate through a reduction area of 75%. Boronizing process was carried out at 1223K for 6 hours, thereafter successfully created surface hardness of 2253HV and 40μm thickness of boronized layer on the DSS. The specimen was then superplastically deformed into a mini gear at 1223K. Result shows surface integrity of the boronized layer deformed at 6 x 10-5 s-1 strain rate and 0.4 mm/mm strain was maintained. As the study progressed, boronized layer demonstrated failure to withstand the increased load when deformed at 1x 10-4 s-1 strain rate. At 6 x 10-5 s-1 strain rate and 1.0 mm/mm strain, the surface disintegrity was associated to high strain factor.